BASIC investment appraisal - Mole, R. H. (London ; Boston : Butterworths, 1985)
This book teaches the relationship of modern computing techniques to soundly based methods of investment appraisal.
Includes index.
rua 27/02/17
Loans.
Keywords: Investments; BASIC (Computer program language)